2016
DOI: 10.1515/jos-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

Interviewer Effects on a Network-Size Filter Question

Abstract: There is evidence that survey interviewers may be tempted to manipulate answers to filter questions in a way that minimizes the number of follow-up questions. This becomes relevant when ego-centered network data are collected. The reported network size has a huge impact on interview duration if multiple questions on each alter are triggered. We analyze interviewer effects on a network-size question in the mixed-mode survey "Panel Study 'Labour Market and Social Security'" (PASS), where interviewers could skip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
(68 reference statements)
1
17
0
1
Order By: Relevance
“…For this survey, in the case of the network size, the intraclass correlation (ICC) was 0.28, which means that 28 percent of the variance in the network size could be attributed to interviewers' characteristics. Similar studies conducted with CAPI mode have found similar or higher ICC Josten and Trappmann (2016). found an ICC of 0.30 in German panel survey "Labour Market and Social Security" (PASS) and Brüderl, Huyer-May and C. Schmiedeberg (2013) an ICC of up to 0.40 for the second wave of German Socioeconomic Panel.…”
supporting
confidence: 60%
“…For this survey, in the case of the network size, the intraclass correlation (ICC) was 0.28, which means that 28 percent of the variance in the network size could be attributed to interviewers' characteristics. Similar studies conducted with CAPI mode have found similar or higher ICC Josten and Trappmann (2016). found an ICC of 0.30 in German panel survey "Labour Market and Social Security" (PASS) and Brüderl, Huyer-May and C. Schmiedeberg (2013) an ICC of up to 0.40 for the second wave of German Socioeconomic Panel.…”
supporting
confidence: 60%
“…We suppose that the interviewer's job experience rises with increasing age what leads to a better understanding of recruiting respondents and thus to a lower nonresponse probability. However, we expect a non-linear relationship as Josten and Trappmann (2016) have found that the response quality decreases with interviewer age. Thus, we also include interviewer age squared.…”
Section: Interviewer Characteristicsmentioning
confidence: 94%
“…To analyse what factors contribute to unit nonresponse, a logistic random-intercept model is estimated (Josten and Trappmann 2016;Rabe-Hesketh and Skrondal 2008) as it is possible that the error terms are correlated across the observations interviewed by the same interviewer.…”
Section: Estimation Methodsmentioning
confidence: 99%
“…Similar studies conducted with CAPI mode have found similar or higher ICC. Josten and Trappmann (2016) found an ICC of 0.30 in German panel survey "Labour Market and Social Security" (PASS) and Brüderl, Huyer-May and C. Schmiedeberg 2013…”
Section: Independent Variablesmentioning
confidence: 99%